ANALISIS PENGARUH FIRM SIZE, LEVERAGE, DEBT TO EQUITY RATIO, DAN RETURN ON EQUITY TERHADAP NILAI PERUSAHAAN (Studi Kasus Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia 2011-2013) (Students' Journal of Accounting and Banking, 2015)
This research was done in order to analyze the effect of the firm size, leverage, Debt to Equity Ratio, and Return On Equity, of Price Book Value. The research objects are food and beverage companies listed in Indonesia Stock Exchange in year 2011-2013. Price Book Value is a ratio which is used to measure the financial activity of a company. PBV also illustrates how much the market appreciates the book value of a stock. The goal of this research was to test the effect of the firm size, leverage, Debt to Equity Ratio, and Return On Equity which was the measurement of Price Book Value. The food and beverage companies listed in Indonesia Stock Exchange in year 2011-2013 was used as the population of this research. It also used purposive sampling technique and got 44 sample companies. The data was tested using normality, multi-colinearity, autocorrelation, and heteroscedasticity. Next, the researcher also used double regression method to know the correlation between variables. The research shown that firm size had negative significant effect towards PBV. The Leverage had negative but insignificant effect, the Debt to Equity Ratio has positive but insignificant effect towards PBV, and the Return On Equity has positive significant effect towards PBV.Keywords: Firm Size, Leverage, Debt to Equity Ratio, Return On Equity and Price Book Value